Aloperine Relieves Type 2 Diabetes Mellitus via Enhancing GLUT4 Expression and Translocation - Song, Guanjun; Huang, Yun; Xiong, Mingrui; Yang, Ziwei; Liu, Qinghua; Shen, Jinhua; Zhao, Ping; Yang, Xinzhou (Frontiers in Pharmacology, 2021)
Aloperine (ALO), a quinolizidine alkaloid isolated from Sophora alopecuroides L. used in the traditional Uygur medicine, induced a significant increase in cellular glucose uptake of L6 cells, suggesting it has the potential to relieve hyperglycemia. Therefore, we investigated the effects of ALO on type 2 diabetes mellitus (T2DM) through in vitro and in vivo studies. The translocation of glucose transporter 4 (GLUT4) and changes in intracellular Ca2+ levels were real-time monitored in L6 cells using a laser scanning confocal microscope and related protein kinase inhibitors were used to explore the mechanism of action of ALO. Furthermore, T2DM rats were induced by high-fat diet combined with low dose streptozotocin and received four weeks intragastric administration of ALO. In vitro results showed that ALO-induced enhancement of GLUT4 expression and translocation were mediated by G protein-PLC-PKC and PI3K/Akt pathways and ALO-increased intracellular Ca2+ was involved in activating PKC via G protein-PLC-IP3R-Ca2+ pathway, resulting in promoted GLUT4 plasma membrane fusion and subsequent glucose uptake. ALO treatment effectively ameliorated hyperglycemia, glucose intolerance, insulin resistance and dyslipidemia, alleviated hepatic steatosis, protected pancreatic islet function and activated GLUT4 expression in insulin target tissues of T2DM rats. These findings demonstrated that ALO deserves attention as a potential hypoglycemic agent.